Implementasi Kelas Rawat Inap Standar Jaminan Kesehatan Nasional Terhadap Sarana Prasarana di RS Wava Husada Malang - As’ady, BJ. Azmy; Yogiyopranoto, Muhammad; Purwadhi, Purwadhi; Widjaja, Yani Restiani (Universitas Pahlawan Tuanku Tambusai, 2025)
National Health Insurance Standard Inpatient Class (KRIS JKN) is a new policy implemented by the Government to improve the quality of health services. There are 12 criteria that are determined in stages, at least 9 of which must be met at the hospital. This research aims to analyze the implementation or application of KRIS JKN at Wava Husada Hospital Malang in 2024. The method used is quasi-qualitative by collecting data through in-depth interviews, documentation and survey instruments. Then the data will be analyzed inductively to build a theory. After carrying out the implementation analysis, it was found that Wava Husada Hospital had met the minimum criteria of 9 criteria, however there were 3 criteria that were still obstacles, including the criteria for bathrooms with accessibility standards and maximum inpatient room density of 4 beds with a distance between the edges of the bed of at least 1, 5 meters at Wava Husada Hospital Malang in 2024.